Answer:66 meters
Step-by-step explanation:
just change the negative to a positive and add them together. It would be 66.
• f(x) = 3x + 4
• g(x) = 8x + 1
Sum both functions above:
(f + g)(x) = f(x) + g(x)
(f + g)(x) = (3x + 4) + (8x + 1)
(f + g)(x) = 3x + 8x + 4 + 1
(f + g)(x) = 11x + 5
Therefore,
(f + g)(0) = 11 · 0 + 5
(f + g)(0) = 0 + 5
(f + g)(0) = 5 <——— this is the answer.
I hope this helps! =)
Answer:
Step-by-step explanation:
y - x = -5
y = x-5
y = 2x² - 3x - 5
x-5 = 2x² - 3x - 5
2x² - 4x = 0
x² - 2x = 0
x(x - 2) = 0
x = 2, 0
(x,y) = (2,-3), (0,-5)
Answer:
Step-by-step explanation:
The Answer is {x| x <-4 or x> 2}